Urban Heat Island Scenarios – A Case study in Technical University, Košice. Issue 4 (December 2020) - Poórová, Zuzana; Li, Heling; Trakal, Lukáš; Vranayová, Zuzana
Abstract: Artificial urban surfaces are commonly considered as main direct cause of Urban Heat Island effects. Most urban land covers are dark and impermeable and accelerating excessive heat absorption and storage. The paper characterizes cool surface strategies in criteria of definition, classification and application approach, as well as proposes of a framework to guide applications associate with grey, blue and green infrastructure on urban heat island mitigation. As a case study, analysis of surface strategy and its cooling performance was performed at Technical University of Košice campus. On perspective of economic and ecological feasibility, two proposals were simulated. The results show that both measures have significant impact on surface cooling, although the maximum and average temperature reductions vary between measures. In addition, overall value of each proposal is provided as reference for decision makers to meet their best interests. All these findings can support climate change adaptation strategy in Kosice, should be also applicable for similar projects and proposals in other regions.